A Sentiment and Content Analysis of Twitter Content Regarding the use of Antibiotics in Livestock - Garrett M Steede; Courtney Meyers; Nan Li; Erica Irlbeck; Sherice Gearhart (Journal of Applied Communications, 2018)
On January 1, 2017, the final rule of the Veterinary Feed Directive (VFD) was put into place requiring antibiotics approved for both humans and animals to be discontinued for growth promotion. This change was brought on by the role growth promoters in livestock production play in the development of antibiotic resistance. Antibiotic resistance increases the costs associated with human health care by increasing the length of stays in the hospital and requiring more intensive medical care for patients. The purpose of this study was to explore sentiment and characteristics of social media content and the characteristics of the key influencers whose opinions had the greatest amount of reach on social media in regard to antibiotic use in livestock and antibiotic resistance. Nuvi, a social media monitoring program, provided sentiment for each tweet and coded 64.8% of the content (n = 129) as negative compared to 38.2% (n = 76) humans coded as negative. The contrast between human coders and Nuvi indicates there could be discrepancies between how Nuvi codes content and the way a human might interpret the content. No key influencer discussed antibiotic use in livestock positively. Findings suggest agricultural communicators should not rely completely on the output from sentiment analysis programs to evaluate how the public discusses issues related to agriculture, particularly controversial issues. Further, agricultural communications practitioners should prioritize monitoring the content shared by key influencers in an effort to better understand the content being shared by the most influential users. Recommendations for future research are provided.
Keywords: Social Media; Content Analysis; Sentiment Analysis; Livestock; Antibiotic